2014
DOI: 10.1097/ta.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital hypertension is predictive of traumatic brain injury and is associated with higher mortality

Abstract: BACKGROUND:The purpose of the current study was to investigate the effect of early adrenergic hyperactivity as manifested by prehospital (emergency medical service [EMS]) hypertension on outcomes of traumatic brain injury (TBI) patients and to develop a prognostic model of the presence of TBI based on EMS and admission (emergency department [ED]) hypertension. METHODS:This study is a retrospective review of the 2007 to 2008 National Trauma Data Bank including blunt trauma patients 15 years or older with availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…However, there have been no major investigations of Cushing’s sign predicting immediate neurosurgical intervention in TBI patients. Previously, many investigators reported the prognostic factors or models in TBI patients at an early stage after injury using vital signs, including GCS or pupillary reaction [4, 5, 12, 14, 15]. Among them, either prehospital hypertension or prehospital hypotension were revealed to be associated with higher mortality due to possible intracranial hypertension or paroxysmal sympathetic hyperactivity and impaired cerebral blood flow [35, 12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there have been no major investigations of Cushing’s sign predicting immediate neurosurgical intervention in TBI patients. Previously, many investigators reported the prognostic factors or models in TBI patients at an early stage after injury using vital signs, including GCS or pupillary reaction [4, 5, 12, 14, 15]. Among them, either prehospital hypertension or prehospital hypotension were revealed to be associated with higher mortality due to possible intracranial hypertension or paroxysmal sympathetic hyperactivity and impaired cerebral blood flow [35, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple logistic regression analysis was performed employing the forced entry method. Odds ratio and 95% confidence interval (CI) for LT-BI in each category based on the pSBP and pHR were described after adjusting for potential confounders including age, gender, chest AIS score (≥4 vs. <4), abdomen AIS score (≥4 vs. <4), and extremity AIS score (≥4 vs. <4), considering patients with pSBP of 100 to 139 mmHg and pHR of 60 to 99 bpm as the reference group [4]. P values of <0.05 were considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Few other studies found a correlation between prehospital hypertension and higher mortality in TBI patients. [18] In our study, mean MAP at admission was 97.23 (±13.97) mm Hg, indicating that many of the patients with isolated TBI patients presented with admission hypertension. Although there are guidelines regarding early management of hypotension, there are no fixed recommendation for identification and treatment of admission hypertension in TBI.…”
Section: Discussionmentioning
confidence: 56%
“…(1925) Excessive blood pressure and blood flow to the brain may exacerbate a TBI by destabilizing intracerebral clots, promoting hemorrhage, and increasing cerebral edema. (24) In a propensity matched study from Japan, patients with head injury and low GCS were more likely to die if treated with REBOA.…”
Section: Discussionmentioning
confidence: 99%